Comparation of Presidential Institutions Between Indonesia and South Korea - Harahap, Roosdiana; Sodikin, Sodikin (Universitas Muhammadiyah Tangerang, 2024)
This study involves a comparison aimed at identifying the similarities and differences in the government systems of the Republic of Indonesia and the Republic of Korea, with a specific focus on the presidential institution. The objective of the study is to compare the key features of these two systems. The research utilizes a comparative method, which involves examining the differences between two or more groups by analyzing various variables (research objects). The findings reveal that the presidential institutions of Indonesia and South Korea share similarities, particularly in the roles of the President as both Head of State and Head of Government, as well as in the process of electing the President. A notable difference lies in the officials who assist the President: in Indonesia, it is the Vice President, while in South Korea, it is the Prime Minister. However, the functions, duties, and authorities of these roles differ significantly. Both countries also share a common approach to filling the presidential office, as Presidents are elected through general elections. Additionally, the mechanism for terminating the President’s office is similar, as both countries utilize impeachment, though the processes and institutions involved in the impeachment procedure differ.Keywords: Comparison, Presidential Institution, Republic of Indonesia, Republic Of Korea, Presidential System